Simple screening protocol for identification of potential mycoremediation tools for the elimination of polycyclic aromatic hydrocarbons and phenols from hyperalkalophile industrial effluents. (1st August 2017) - Batista-García, Ramón Alberto; Kumar, Vaidyanathan Vinoth; Ariste, Arielle; Tovar-Herrera, Omar Eduardo; Savary, Olivier; Peidro-Guzmán, Heidy; González-Abradelo, Deborah; Jackson, Stephen A.; Dobson, Alan D.W.; Sánchez-Carbente, María del Rayo; Folch-Mallol, Jorge Luis; Leduc, Roland; et al.
Abstract: A number of fungal strains belonging to the ascomycota, basidiomycota and zygomycota genera were subjected to an in vitro screening regime to assess their ligninolytic activity potential, with a view to their potential use in mycoremediation-based strategies to remove phenolic compounds and polycyclic aromatic hydrocarbons (PAHs) from industrial wastewaters. All six basidiomycetes completely decolorized remazol brilliant blue R (RBBR), while also testing positive in both the guaiacol and gallic acid tests indicating good levels of lignolytic activity. All the fungi were capable of tolerating phenanthrene, benzo-α- pyrene, phenol and p -chlorophenol in agar medium at levels of 10 ppm. Six of the fungal strains, Pseudogymnoascus sp., Aspergillus caesiellus, Trametes hirsuta IBB 450, Phanerochate chrysosporium ATCC 787, Pleurotus ostreatus MTCC 1804 and Cadophora sp. produced both laccase and Mn peroxidase activity in the ranges of 200–560 U/L and 6–152 U/L, respectively, in liquid media under nitrogen limiting conditions. The levels of adsorption of the phenolic and PAHs were negligible with 99% biodegradation being observed in the case of benzo-α-pyrene, phenol and p -chlorophenol. The aforementioned six fungal strains were also found to be able to effectively treat highly alkaline industrial wastewater (pH 12.4). When this wastewater was supplemented with 0.1 mM glucose, all of the tested fungi, apart from A. caesiellus, displayed the capacity to remove both the phenolic and PAH compounds. Based on their biodegradative capacity we found T. hirsuta IBB 450 and Pseudogymnoascus sp., to have the greatest potential for further use in mycoremediation based strategies to treat wastestreams containing phenolics and PAHs. Graphical abstract: Highlights: Mycoremediation is a powerfull tool to remove aromatic compounds from wastewaters. Aromatic compounds were removed under highly alkaline conditions (pH 12). The tested strains have high abilities to remove pyrene, phenantrene and phenols. These fungi can emerge as efficient and trustworthy tools for wastewater treatment.